Victimological Approaches to Crime of Rape in Indonesian Criminal Justice System - Dimyati, Khudzaifah; Angkasa, Angkasa (Hasanuddin University, 2018)
Neglect of rape victims in the Indonesian Criminal Justice System implicates at least two things; first, the victim does not receive legal protection, and second, the decisions of judges do not fulfill the sense of justice. Neglect of victims in the Criminal Justice System cannot be separated from the theory, doctrine and legislation, especially criminal law or the Penal Code, Criminal Procedure Code and the Corrections Act, which is oriented merely to the perpetrators (criminal oriented) instead of victims (victim oriented). Regarding the conditions above, this study was intended to provide a solution of the problems so that victims in the Criminal Justice System obtain legal protection and the decision of judges could fulfill the sense of justice.